Comparison of the Mean Cross-sectional Area of the Median Nerve between Pregnant and Non-Pregnant Women Using Ultrasonography in a Tertiary Level Hospital, Nepal - Adhikari, G; Regmi, PR; Paudel, S; Lamichhane, B; Kayastha, P; Maharjan, S; Amatya, I (Kathmandu University Medical Journal, 2023)
Background The median nerve is subjected to compression in the carpal tunnel giving rise to a constellation of symptoms known as carpal tunnel syndrome. It is the most frequent form of peripheral entrapment neuropathies and is most prevalent in the middle age females. The most common cause of this syndrome is idiopathic. One of the known secondary causes is pregnancy. Objective To compare the mean cross sectional area of median nerve using ultrasound in pregnant and non-pregnant females at carpal tunnel inlet and its variations with different trimesters. Method The study was conducted during a period of one year (October 2014 to September 2015). A total of 204 participants were evaluated among which 102 were nonpregnant and 102 were pregnant. Among the 102 pregnant participants, 34 females each were in the first, second, and third trimesters. A convenience sampling technique was used for the selection of the participants. The mean cross-sectional area of the median nerve was calculated in both of these groups in both hands by using the direct method. The mean cross-sectional area of non-pregnant female was used as the reference value to which that of pregnant female were compared. Data obtained were compiled and analyzed using Statistical Package for Social Sciences Version 16. Result The overall mean cross-sectional area of the median nerve in non-pregnant females was 6.76 ± 1.05 mm2 and in pregnant females was 6.84 ± 1.09 mm. No statistically significant difference was noted in the mean cross-sectional area of the median nerve in either hand in both pregnant and non-pregnant females. No statistically significant difference was noted in the overall mean cross-sectional area between the non-pregnant and pregnant females. There was no significant difference in the mean cross-sectional area within the different trimesters in both hands on intergroup comparisons. Conclusion Ultrasound examination of the median nerve and measurement of its cross-sectional area is a useful diagnostic tool in the evaluation of carpal tunnel syndrome. Ultrasound has the advantage of easy availability, low cost, quick scan time, able to scan a long segment of nerve and examine the structures in both static and dynamic states. Besides, it also helps in the identification of various anatomic variants and pathologies within or adjacent to carpal tunnel.